Productivity Analysis Using the Marvin E. Mundel Method on Pd. Sumber Marka Jaya - Roban, Roban; Suryadi, Suryadi; Suhara, Ade; Hermawan, Asep (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
This study aims to analyze work productivity in PD. Source: Marka Jaya using the Marvin E. Mundel method approach which is known to be effective in measuring the efficiency and effectiveness of the production system. This research is motivated by the need to increase productivity to increase the competitiveness of companies in the midst of increasingly fierce competition in the furniture industry. The data collected includes various inputs and outputs of production in 2022 and 2023, such as labor use, raw materials, energy, and maintenance and machine usage. The results show that the value of the productivity index has fluctuated throughout 2023, with the highest value of 1.82 occurring in January and the lowest value of 0.23 in April. Factors influencing these changes include efficient use of raw materials, optimal labor management, and regular maintenance of machinery. Based on the results of the analysis, it is recommended that companies conduct periodic evaluations of the production process, improve workforce skills, and adopt appropriate technology to support work efficiency. This research makes a practical contribution to company management in formulating strategies to increase productivity in a sustainable manner.